Crystal structure of pantoprazole sodium sesquihydrate Form I, C16H14F2N3O4SNa(H2O)1.5. Issue 1 (March 2020) - Gonzalez, Diana; Golab, Joseph T.; Kaduk, James A.; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of pantoprazole sodium sesquihydrate has been solved and refined using synchrotron X-ray powder diffraction data and optimized using density functional techniques. Pantoprazole sodium sesquihydrate crystallizes in space group Pbca (#61) with a = 33.4862(6), b = 17.29311(10), c = 13.55953(10) Å, V = 7852.06(14) Å 3, and Z = 16. The crystal structure is characterized by layers parallel to the bc -plane. One layer contains the Na coordination spheres. The two independent sodium ions are trigonal bipyramidal and octahedral. The NaO3 N2 and NaO4 N2 coordination spheres share an edge to form pairs. The sodium bond valence sums are 1.17 and 1.15. The difluoromethyl groups are probably disordered. Two water molecules act as hydrogen bond donors to pyridine nitrogen atoms and sulfoxide oxygen atoms. The third water molecule participates in bifurcated hydrogen bonds, but one of its hydrogen atoms does not participate in hydrogen bonds. The powder pattern is included in the Powder Diffraction File™ as entry 00-065-1424.